Răspuns :
a=[tex] \frac{5}{3} [/tex]-[tex] \frac{3}{7} [/tex]=[tex] \frac{35-9}{21} [/tex]=[tex] \frac{26}{21} [/tex]
b=[tex] \frac{1}{3} [/tex]+[tex] \frac{3}{7} [/tex]=[tex] \frac{7+9}{21} [/tex]=[tex] \frac{16}{21} [/tex]
ma=[tex] \frac{a+b}{2} [/tex]=[tex] \frac{26}{21}+ \frac{16}{21} [/tex] supra 2=[tex] \frac{26+16}{21} [/tex] supra 2=[tex] \frac{42}{21} [/tex] supra 2=[tex] \frac{42}{21} [/tex] x [tex] \frac{1}{2} [/tex]=[tex] \frac{42}{42} [/tex]=1
b=[tex] \frac{1}{3} [/tex]+[tex] \frac{3}{7} [/tex]=[tex] \frac{7+9}{21} [/tex]=[tex] \frac{16}{21} [/tex]
ma=[tex] \frac{a+b}{2} [/tex]=[tex] \frac{26}{21}+ \frac{16}{21} [/tex] supra 2=[tex] \frac{26+16}{21} [/tex] supra 2=[tex] \frac{42}{21} [/tex] supra 2=[tex] \frac{42}{21} [/tex] x [tex] \frac{1}{2} [/tex]=[tex] \frac{42}{42} [/tex]=1